Pengaruh Penerapan Metode Hypnoteaching terhadap Motivasi Belajar Mahasiswa Universitas Indraprasta PGRI - Hasbullah Hasbullah; Eva Yuni Rahmawati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
The aim of the study was to determine the effect of hypnoteaching learning methods on students’ motivation in learning English at mathematics epartment. Experiment was conducted on a sample of 90 students at mathematics department in UNINDRA PGRI. Data collection was performed by administering treatment hypnoteaching learning methods and by implementing pratest and post test students' learning motivation. Analysis of research data using unpaired t-test Data invitation SPSS Version 16. The finding suggest that there are significant effects of hypnoteaching methods on students’ motivation to learn English at mathematics department in UNINDRA PGRI. Keywords: learning methods, hypnoteaching, motivation to learn, english.